A Collective Self-Study to Improve Program Coherence of Clinical Experiences. Issue 2 (3rd May 2016) - Samaras, Anastasia P.; Frank, Toya Jones; Williams, Monique Apollon; Christopher, Emily; Rodick, William Harry
Abstract: Student feedback collected through program evaluation of secondary education licensure and Master's program clinical experiences prompted us to conduct a collective self-study. We used a reflective framework for analysis and discussion of the shifts students in our courses made as they progressed from observers to practicing teachers. Along with our graduate students, we collected and shared data and analysis from two courses – an introductory mathematics course for pre-service teachers and a capstone self-study teacher research course for in-service teachers. Data included students' reflective accounts of their clinical experiences, dialogue with peers in response memos and focus groups, and our meta-conversation about and interpretations of data captured in meeting notes, audio recordings of meetings, email exchanges, and video conferencing over a two-month period. Analysis resulted in reframed thinking about our teaching and implications for program coherence, including provision of meaningful participant observations in diverse settings, design of dialogic platforms for students to make connections, and support of a critical level of reflection to inform teacher professional practice. The results are informative to teacher educators and programs seeking to better understand their roles in designing dialogic spaces for students to think deeply about the connections of their courses to clinical experiences and in supporting ongoing teacher professional development. The study highlights the benefits of faculty collective self-studies and contributes to the literature on self-study for program development.